2018
DOI: 10.1016/j.jacep.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of a High-Frequency Jet Ventilation Strategy for Catheter Ablation for Atrial Fibrillation

Abstract: OBJECTIVES The aim of the current investigation is to examine whether use of high-frequency jet ventilation (HFJV) during pulmonary vein isolation (PVI) performed with force-sensing catheters is associated with improved outcomes. BACKGROUND Catheter ablation is well established as therapy for symptomatic atrial fibrillation (AF). Reconnection following PVI is commonly observed during repeat ablation procedures. Technologies that may optimize catheter stability and lesion delivery include both force-sensing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 14 publications
(21 reference statements)
1
32
0
Order By: Relevance
“…Rapid pacing has been shown to reduce the standard deviation in force by less than 1 g compared to its nonpaced counterpart, and its effectiveness is dependent on regional anatomical location within the LA . In a study examining almost 30 000 RF applications, HFJV only reduced force variability index by 0.06 on average in comparison with normal ventilation . In contrast, to achieve optimal force variability based on the variability criteria of CFV (<5 g ) and RSD (<30%), the CFC reduced standard deviation in the force profiles by 6.3 g on average and the force variability index by 0.21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid pacing has been shown to reduce the standard deviation in force by less than 1 g compared to its nonpaced counterpart, and its effectiveness is dependent on regional anatomical location within the LA . In a study examining almost 30 000 RF applications, HFJV only reduced force variability index by 0.06 on average in comparison with normal ventilation . In contrast, to achieve optimal force variability based on the variability criteria of CFV (<5 g ) and RSD (<30%), the CFC reduced standard deviation in the force profiles by 6.3 g on average and the force variability index by 0.21.…”
Section: Discussionmentioning
confidence: 99%
“…Systolo‐diastolic cardiac motion and respiration are the primary contributors to variability in contact force . Clinical techniques used to mitigate their effect include rapid atrial pacing, high‐frequency jet ventilation (HFJV), and induced apnea . Rapid pacing has been shown to reduce the standard deviation in force by less than 1 g compared to its nonpaced counterpart, and its effectiveness is dependent on regional anatomical location within the LA .…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received HFJV had decreased incidence of acute and chronic pulmonary vein reconnection and required fewer repeat procedures at 1 year 10 . Another study demonstrated a decreased rate of arrhythmia recurrence with HFJV, though the effect was only significant in ablations for paroxysmal atrial fibrillation and not for persistent atrial fibrillation 11 …”
Section: Discussionmentioning
confidence: 99%
“…Further, investigators reported a significant improvement was achieved in the maintenance of a level of contact force of more than 5 g and a higher mean force variability index was realized with HFJV in comparison with standard ventilation (p ≤ 0.001), facilitating improved lesion delivery and ablation-line integrity. 25 Prior to this study, Kumar et al demonstrated the benefit of catheter stability afforded by regulating ventilation and reported significant improvement in the average force-time integral during apnea as compared with standard ventilation. 26 While these studies focused on atrial ablations, the conceptual experience is potentially applicable to ventricular ablations as well, although we are unaware of any trials using the principle of HFJV during VT ablation published at this time.…”
Section: Discussionmentioning
confidence: 91%